PERAN CSR (CORPORATE SOCIAL RESPONSIBILITY) “SAVE THE CHILDREN (STC)” DALAM MENDUKUNG PEMBIAYAAN PENDIDIKAN BERKELANJUTAN DI SMPN 3 RANCAEKEK: DI SMPN 3 RANCAEKEK - Helmawati, Helmawati; Suherman, Maman; Mulhima Prihatini, Ima; Komalasari, Kokom (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education plays a vital role in sustainable development, and the business world through CSR (Corporate Social Responsibility) programs can expand access, improve quality, and encourage empowerment through leadership development and education. The purpose of this study is to obtain information or an overview and analyze the role of CSR (Corporate Social Responsibility) "Save the Children" in supporting sustainable education financing at SMPN 3 Rancaekek which focuses on the planning, implementation, evaluation, and follow-up plan processes. This study uses a qualitative approach with a case study method. Data collection techniques through observation, interviews, and documentation studies. Data validity through triangulation techniques, member checks, and conformability. Data analysis techniques through data reduction, data presentation, and drawing conclusions and verification. The results of the study illustrate that in the planning stage (Plan), it begins with holding a meeting and coordination between Save the Children (STC) and the school. In the implementation stage (Do), Save the Children (STC) provides several assistance to the school, including providing training, providing a place to sort organic and inorganic waste, plant seeds for reforestation, and also building infiltration wells to minimize flooding. In the evaluation stage (Check), the evaluation is carried out at the end of each assistance program provided by Save the Children (STC). The evaluation is carried out by the school with Save the Children (STC) to measure the extent of the success of the program that has been implemented. As a follow-up plan (Act), a student community was formed called the STOPS community (Sahabat Tanaman and Operasi Potongan Sampah). CSR (Corporate Social Responsibility) "Save the Children (STC)" through several programs has supported the financing of sustainable education at SMPN 3 Rancaekek.